PEMBERDAYAAN MASYARAKAT MELALUI IbM PELATIHAN OLAHAN LIMBAH TAHU DI DESA DRONO NGAWEN KLATEN - Nur Azis Rohmansyah; Fafa Nurdyansyah; Bertika Kusuma Prastiwi (Jurnal Kewirausahaan dan Bisnis, 2017)
This community empowerment activity through science andtechnology program for the community aims to increase the knowledge ofthe community at Drono village, Ngawen Klaten regency of Central Java.,especially the women in processing and utilizing solid waste in makingnuggets, tempeh, and milk which is economically valuable andencouraging people to create new business to increase the income ofsurrounding communities. The methods used are socialization andcounseling, waste utilization training, production management andfinancial administration, program discussions and evaluation. Theactivity was held at the residence of one of Drono Ngawen villagers with25 women. During the activity all participants were very enthusiastic, allparticipants were also given material about the utilization of tofuproduction waste to be processed into economic value products. Eachparticipant is equipped with guidance about management of onlinemarketing and finance, also coaching about establishment new efforts toimprove skills and knowledge.Keywords: tofu waste, training, management, bussiness, IbM